ASNAF ENTREPRENEUR AL-FALAH MODEL BASED ON THE SUNNAH PRACTICES OF RASULULLAH PBUH - Syamimi Ahmad; Zuraidah Mohamed Isa; Daing Maruak Sadek (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
Entrepreneurship is an important element of economic development and progress for a country. This article discusses the success factors of asnaf entrepreneurs that are closely related to the sunnah practices of Rasulullah pbuh. The findings of the literature review pertaining Islamic spiritual practices show that the sunnah practices of Rasulullah pbuh can influence the success of asnaf entrepreneurs. This study focuses on the sunnah practices of Rasulullah pbuh among asnaf entrepreneurs. In this regard, in addition to conducting business and making profit, asnaf entrepreneurs also need to apply religious values in order to fulfil needs, gain the pleasure of Allah, and gain blessings in their profit. Asnaf entrepreneurs are encouraged to emulate Rasulullah pbuh’s traits, namely siddiq, amanah, fathanah, and tabligh, and make them as benchmarks in sale and purchase transactions. The study used the qualitative method whereby library study were applied for data collection. The researcher found that attaining Al-Falah (success) requires instilling several important elements of the traits of Rasulullah pbuh to shape the personality of asnaf entrepreneurs. Society also needs to support asnaf entrepreneurs in practising those traits in business transactions. The exploration of Islamic personality building among asnaf entrepreneurs has distinctive implications, particularly in improving the asnaf entrepreneur Islamic model.